Micro e pequenas empresas para sempre?: desafios para o Brasil - Grof, Rogério Aparecido (2017)
Micro and small business have been increasingly concerning governments globally, as they act like social cushion due to the large number of jobs they are responsible for. Despite this, many countries have not yet been capable of developing public policies to effectively support the development of these enterprises. The Brazilian Federal Constitution of 1988, in its articles 170 and 179 of the Economic Order Chapter, gives them favored and differentiated treatment. Almost thirty years after C.F./88’s promulgation, and already with an infraconstitutional legislative set developed for small companies, they are still not important factors in promoting the Brazilian economy development. Was the constitutional treatment given to small businesses an attempt to generate public policies, or merely populist rhetoric?As a condition to the creation of public policies, it is necessary to define both the object and scope of these policies. In Brazil, though, there is still great confusion in the understanding of what a small company is. What is a small business after all? With that uneasiness, it can be of great value to study how these definitions are made, and what goals they pursuit in the most developed economy of the planet – The United States of America. It is also intended to study the US agency responsible for coordinating the country’ state policies related to small businesses, the Small Business Administration, and how actions to ensure the competitiveness of North American Small and Micro Enterprises work. This paper therefore aims to study the institutionalization of small enterprises in the United States of America and how they are part of the economy structure of that country. It is also intended to criticize the current treatment’ structure given to small Brazilian companies and to point out alternatives for the transformation of the national status quo, with the real inclusion of small companies as protagonists in the modernization and evolution of the Brazilian economy.